Improving the Level of Communication Development of Students - Nigora Mahmudovna Djampulatova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, we examine each component of the methodology for enhancing students' communicative competence in the context of coaching. We broke down this process into several stages, indicating the gradual application of techniques meant to raise students' level of communicative development.